Efektifitas Media Video Animasi dalam Peningkatan Pengetahuan tentang HIV pada Siswa/I di SMPN 24 Bekasi - Rahmawati, Dwi; Mulyanto, Tatag (Universitas Malahayati, 2025)
ABSTRACT HIV/AIDS is the biggest health problem found almost all over the world. The lack of information about HIV AIDS in adolescents can lead to promiscuity that leads to the transmission of HIV/AIDS infectious diseases, so it is necessary to provide information to help adolescents understand and realize how dangerous HIV/AIDS is. To find out the effectiveness of animated videos on increasing knowledge about HIV AIDS in students of SMPN 24 Bekasi. This study uses a quantitative research design with an experimental quasy research design of one group pretest post test design. The sample in this study is 80 students of SMPN 24 Bekasi. Data was obtained using a questionnaire and analyzed using the Paired Sample T-Test. The study showed that there was an effect of the effectiveness of anisami videos on increasing knowledge about HIV AIDS in students of SMPN 24 Bekasi with a p-value of 0.000 (<0.05). HIV/AIDS is the biggest health problem found almost all over the world. The lack of information about HIV AIDS in adolescents can lead to promiscuity that leads to the transmission of HIV/AIDS infectious diseases, so it is necessary to provide information to help adolescents understand and realize how dangerous HIV/AIDS is. To find out the effectiveness of animated videos on increasing knowledge about HIV AIDS in students of SMPN 24 Bekasi. This study uses a quantitative research design with an experimental quasy research design of one group pretest post test design. The sample in this study is 80 students of SMPN 24 Bekasi. Data was obtained using a questionnaire and analyzed using the Paired Sample T-Test. The study showed that there was an effect of the effectiveness of anisami videos on increasing knowledge about HIV AIDS in students of SMPN 24 Bekasi with a p-value of 0.000 (<0.05). Therefore, it can be concluded that the effectiveness of animated video media in increasing knowledge about HIV in students at SMPN 24 Bekasi in 2024, therefore, it is hoped that it can be used as an alternative choice of health education media for providing information in conveying education about adolescent sex. Keywords: HIV AIDS, Knowledge, Animated Videos ABSTRAK HIV/AIDS merupakan masalah kesehatan terbesar yang terdapat hampir diseluruh dunia. Kurangnya informasi tentang HIV AIDS pada remaja dapat menjerumuskan pada pergaulan bebas yang mengarah terhadap penularan penyakit menular HIV/AIDS, sehingga perlu dilakukan pemberian informasi untuk membantu agar remaja memahami dan menyadari seberapa berbahayanya HIV/AIDS. Untuk mengetahui efektivitas video animasi terhadap peningkatan pengetahuan tentang HIV AIDS pada siswa/i SMPN 24 Bekasi. Penelitian ini menggunakan kuantitatif dengan desain penelitian quasy eksperiment one group pretest post test desain. Sampel dalam penelitian ini yaitu siswa/i SMPN 24 Bekasi sebanyak 80 orang siswa. Data diperoleh dengan menggunakan kuesioner dan dianalisis menggunakan Uji Paired Sample T-Test. Penelitian menunjukkan adanya pengaruh efektivitas video anisami terhadap peningkatan pengetahuan tentang HIV AIDS pada siswa/i SMPN 24 Bekasi dengan p-value 0,000 (<0,05). Sehingga dapat disimpulkan bahwa adanya Efektifitas Media Video Animasi Dalam Peningkatan Pengetahuan Tentang HIV Pada Siswa/i Di SMPN 24 Bekasi Tahun 2024, oleh karena itu, diharapkan dapat dijadikan pilihan alternatif media edukasi kesehatan untuk pemberian informasi dalam menyampaikan edukasi tentang seks remaja. Kata Kunci: HIV/AIDS, Pengetahuan, Video Animasi